Formation of mathematical models of balancing installations measuring systems - Burbelo, M. Y.; Babenko, O. V. (Visnyk of Vinnytsia Politechnical Institute, 2010)
Mathematical models for design of balancing installations measuring systems applied in two approaches for voltage balancing in the node of consumer connection: usage of balancing installations units with phase control of balancing transformer.